In Vivo Electroporation of Plasmid DNA: A Promising Strategy for Rapid, Inexpensive, and Flexible Delivery of Anti-Viral Monoclonal Antibodies - Silvere Pagant; Rachel A. Liberatore (MDPI AG, 2021)
Since the first approval of monoclonal antibodies by the United States Food and Drug Administration (FDA) in 1986, therapeutic antibodies have become one of the predominant classes of drugs in oncology and immunology. Despite their natural function in contributing to antiviral immunity, antibodies as drugs have only more recently been thought of as tools for combating infectious diseases. Passive immunization, or the delivery of the products of an immune response, offers near-immediate protection, unlike the active immune processes triggered by traditional vaccines, which rely on the time it takes for the host's immune system to develop an effective defense. This rapid onset of protection is particularly well suited to containing outbreaks of emerging viral diseases. Despite these positive attributes, the high cost associated with antibody manufacture and the need for a cold chain for storage and transport limit their deployment on a global scale, especially in areas with limited resources. The in vivo transfer of nucleic acid-based technologies encoding optimized therapeutic antibodies transform the body into a bioreactor for rapid and sustained production of biologics and hold great promise for circumventing the obstacles faced by the traditional delivery of antibodies. In this review, we provide an overview of the different antibody delivery strategies that are currently being developed, with particular emphasis on in vivo transfection of naked plasmid DNA facilitated by electroporation.